Value to customer and company goals - Theoretical considerations - Kozieł, Paulina (Humanities & Social Sciences Reviews, 2023)
Purpose of the study: The main goal of this study is to present selected aspects of customer value, taking into account its importance for the company’s operation, based on the analysis of domestic and foreign literature on the subject. Methodology: The research method used in the article is the method of literature analysis and criticism. The following research techniques were used in the study: analysis of domestic and foreign literature on the subject, analysis of source documents (existing sources) - desk research, and inference methods (deduction and induction). Main findings: Creating value for the customer is important in achieving market success for the company. By learning about the needs, expectations, and requirements of customers regarding the products and services offered by the company, the offer can be more precisely tailored to them, which will ultimately contribute to a competitive advantage. Creating value and providing it to customers should therefore be one of the key factors that a company should include in its system of goals to achieve satisfactory financial results. Application of the study: This article shows customer values’ importance in formulating company goals. The considerations presented in the study do not exhaust all the issues discussed. The considerations presented will be the basis for further theoretical analyzes and empirical research in this area. Originality/Novelty of the study: The issue of customer value as an important factor related to setting company goals is not new in the literature. However, it is so important from the point of view of business practice that it requires permanent in-depth analysis.